(untitled) - Kanter, Rosabeth Moss (New York, 2004)
The author looks at winning and losing in the business world, arguing that the key to success lies in an organization's character, perseverance, winning tradition, and confidence.
Keywords: English language,Ngôn ngữ Anh; Study and teaching,Học và dạy